Evaluation of Transcriptomic Responses in Livers of Mice Exposed to the Short-Chain PFAS Compound HFPO-DA - Heintz, Melissa M.; Chappell, Grace A.; Thompson, Chad M.; Haws, Laurie C. (Frontiers in Toxicology, 2022)
HFPO-DA (ammonium 2,3,3,3-tetrafluoro-2-(heptafluoropropoxy)-propanoate; CASRN 62037-80-3) is a component of the GenX technology platform used as a polymerization aid in the manufacture of some types of fluoropolymers. The liver is the primary target of toxicity for HFPO-DA in rodents and previous examination of hepatic transcriptomic responses in mice following oral exposure to HFPO-DA for 90 days showed induction of peroxisome proliferator-activated receptor signaling pathways, predominantly by PPARα, as well as increased gene expression of both peroxisomal and mitochondrial fatty acid metabolism. To further investigate the mechanism of liver toxicity, transcriptomic analysis was conducted on liver tissue from mice orally exposed to 0, 0.1, 0.5 or 5 mg/kg-bw/day HFPO-DA in a reproduction/developmental toxicity study. Hepatic gene expression changes demonstrated activation of the PPARα signaling pathway. Peroxisomal and mitochondrial fatty acid β-oxidation gene sets were enriched at lower HFPO-DA concentrations, and complement cascade, cell cycle and apoptosis related gene sets were enriched at higher HFPO-DA concentrations. These results support the reported histopathological findings in livers of mice from this study and indicate that the effects of HFPO-DA are mediated through rodent-specific PPARα signaling mechanisms regardless of reproductive status in mice.